EFFECTS OF THE RUSSIA-UKRAINE WAR ON TÜRKİYE’S FOREIGN TRADE AND TOURISM SECTOR - Catuk, Cuneyt (My University, 2023)
With the introduction of political and economic penalties, wars between nations now take on a new dimension. Unlike the First and Second World Wars, as portrayed by political personalities, the Third World War tries to neutralize each other through economic penalties. The most recent examples of this include the recent conflict between Russia and Ukraine and the sanctions put on Russia by the United States, the European Union, and other nations. This study aims to analyze the impact of the war between Russia and Ukraine on Turkey's foreign trade. The common category that Turkey imports most from Ukraine and Russia is cereals. In this chapter, the conflict will have the greatest impact on Turkey. The impact of the current conflict between Russia and Ukraine on the Turkish economy is examined in this study using information from the Turkish Statistical Institute (TurkStat) and the Ministry of Culture and Tourism. As a result of the study, despite Turkey's reliance on Russia and Ukraine, its most significant advantage is that it is not reliant on raw material exports and has a diverse product infrastructure.
Keywords: Foreign Trade; Grain; Sanctions